2007
DOI: 10.1103/physrevb.76.045422
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure and velocity of field-driven solid-on-solid interfaces moving under a phonon-assisted dynamic

Abstract: The nanoscopic structure and the stationary propagation velocity of ͑1+1͒-dimensional solid-on-solid interfaces in an Ising lattice-gas model, which are driven far from equilibrium by an applied force, such as a magnetic field or a difference in ͑electro͒chemical potential, are studied by an analytic nonlinear-response approximation ͓P. A. Rikvold and M. Kolesik, J. Stat. Phys. 100, 377 ͑2000͔͒ together with kinetic Monte Carlo simulations. Here, we consider the case that the system is coupled to a two-dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
(110 reference statements)
0
12
0
Order By: Relevance
“…When applied to kinetic Ising lattice-gas models, soft and hard Arrhenius dynamics give very different nucleation rates [11]. It has also recently been shown that SOS interfaces evolving under soft Arrhenius dynamics have quite different structures that those evolving under hard Arrhenius dynamics [7]. In soft Arrhenius dynamics, the barrier height only results in a change in the overall time scale of the simulation and has no effect on the interface microstructure [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When applied to kinetic Ising lattice-gas models, soft and hard Arrhenius dynamics give very different nucleation rates [11]. It has also recently been shown that SOS interfaces evolving under soft Arrhenius dynamics have quite different structures that those evolving under hard Arrhenius dynamics [7]. In soft Arrhenius dynamics, the barrier height only results in a change in the overall time scale of the simulation and has no effect on the interface microstructure [7].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently it was commonly believed that dynamics that respect the same conservation laws and all obey detailed balance, give essentially the same qualitative behavior. However, recent results clearly show that there are nonconservative dynamics that, although they all obey detailed balance and the same conservation laws, lead to very different interface microstructures [3,4,5,6,7]. Since many interface properties, such as mobility and chemical activity, are determined by the microstructure, great care must therefore be taken in selecting the appropriate dynamic for the physical or chemical system of interest.…”
Section: Introductionmentioning
confidence: 99%
“…A similar feature was reported in the time evolution of field-driven solid-on-solid interfaces using the d = 2 phonon-assisted transition rate. 22 Monte Carlo simulations are performed for D =4J and H = 0 with periodic boundary conditions and a random initial state. Spins at sites are updated in a regular typewriter fashion.…”
Section: B Equilibrium Propertiesmentioning
confidence: 99%
“…Very recently, the derived phonon-assisted transition rates were used to examine the nanostructure of field-driven solid-on-solid interfaces. 22 It was found that the phonon-assisted rates provide significant differences from other types of transition rates, such as the Glauber dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Other commonly used dynamics are Metropolis [27] and soft stochastic dynamics [28]. It has been shown that different dynamics demand even different interpretations of the Arrhenius law [29] as well as different nonequilibrium properties [30] in the Ising model and nanostructures of field-driven solid-on-solid interfaces. One of us derived a transition rate or dynamic from a microscopic model where a spin system (S 1 generalized BC model) is weakly coupled to a d-dimensional phonon bath [31].…”
Section: Introductionmentioning
confidence: 99%